Correlation of chromogranin A levels and somatostatin receptor scintigraphy findings in the evaluation of metastases in carcinoid tumors - Sirianong Namwongprom (2018)
Objective: Chromogranin A (CgA) has been gaining acceptance as a helpful tumor marker in patients with neuroendocrine tumors, with respect to both diagnosis and prognosis. The objective of this study was to correlate serum CgA levels and somatostatin receptor scintigraphy (SRS) findings in the evaluation of metastases in carcinoid tumors. Materials and methods: A total of 125 patients(61 men and 64 women, aged from 23 to 84 years) with histologically diagnosed carcinoid tumor underwent serum CgA assay and SRS for detecting metastasis or disease recurrence. The quantitative determination of CgA was performed in serum using an enzyme immunoassay with a cut-off value fixed at 39 U/l. Scintigraphies were performed with 200-220 MBq of In-111-DTPA-Phel- octreotide including whole-body images as well as single-photon emission computed tomography and computed tomography scans of the chest and abdomen. Results: The primary tumors originated from the gastrointestinal tract in 115 of 125 patients (92.0%), the lung in 7 of 125 patients (5.6%), the kidney in 2 of 125 patients (1.6%), and the breast in 1 of 125 patients (0.8%). The primary tumors originated from the foregut, midgut, and hindgut in 13.6%, 71.2%, and 12.8%, respectively. Correlation of SRS with other imaging modalities and clinical follow-up findings revealed a sensitivity, a specificity, and an accuracy of 82.9%, 97.7%, and 88.0%, respectively, and for CgA 62.2%, 83.7%, and 69.6%, respectively. There was 1 false-positive and 14 falsenegative SRS results and 7 false-positive and 31 falsenegative CgA analyses. SRS demonstrated higher sensitivity, specificity, and accuracy than CgA for the evaluation of metastatic carcinoid tumors. The concordance between SRS and CgA results was 67.2%. Discrepancies, such as positive SRS with normal CgA levels, were noted in 26 (20.8%) cases, whereas negative SRS with high CgA levels was seen in 15 (12.0%) cases. Combining the results of CgA and SRS increased the sensitivity (92.7%) but decreased the specificity (81.4%) of tumor detection. Conclusions: In our study, SRS proved to be more sensitive, more specific, and more accurate than CgA for metastatic evaluation of carcinoid tumors. Positive SRS correlated with elevation of serum CgA levels. Serum CgA might have some diagnostic utility in patients with negative SRS studies. Nevertheless, both SRS and CgA should be considered useful tools in the evaluation of metastases in carcinoid patients. © 2008 The Japanese Society of Nuclear Medicine.